Toward a Research Agenda for Rural Education: Discovering the Essence - Russel L. Dobson; Judith E. Dobson (Journal of Research in Rural Education, 1987)
Three realities (mindscapes) used in constructing knowledge and their traditional research methodologies are discussed as a basis for proposing a research agenda and strategy for rural education. In order to study rural education, the authors propose the use of conceptual empiricism and contextual appraisal consisting of four domains; personal (self), instruction (class), institutional (school), and societal (schooling). Data are collected in each of these domains in order to discover the essence, to 'paint a portrait,' of the rural school. Within each of these domains, three research tools (currere, hegemony, and connoisseurship) are suggested as means of viewing the rural school from a holistic perspective and placing the research emphasis upon emergent patterns rather than manipulated variables. Once the portrait of the rural school is unveiled, then suggestions for improvement (if needed) can be discussed.